John Cunningham, The Consort Music of William Lawes 1602-1645 (2010) - Howard, Alan (Journal of the Society for Musicology in Ireland, 2012)
A review of John Cunningham, The Consort Music of William Lawes 1602-1645 (Woodbridge: Boydell, 2010). ISBN 978-0-9546-8097-8.